FORMULATION AND EVALUATION OF CETIRIZINE HYDROCHLORIDE pH TRIGGED IN-SITU OCULAR GEL - SAURABH, SURENDRA SINGH; RATHORE, KAMAL SINGH; GHOSH, SANTANU (International Journal of Applied Pharmaceutics, 2023)
Objective: In the present research work, the aim was to prepare pH trigged in-situ ocular gel of Cetirizine Hydrochloride (CTZ) to improve its local bioavailability at the eye surface. Methods: CTZ in-situ ocular gel was prepared by the pH-trigged method. In-situ CTZ ocular gel was prepared by a pH-sensitive gelling agent (Carbomer) with a one-viscosity builder polymer (HPMC E4M). All formulation was evaluated for appearance, pH, viscosity at different pH, gelling capacity, % drug content, and drug release. Nine formulations were prepared and optimized successfully using 32 factorial designs. Optimization was done by DoE software version Version 13.0.10.064. Results: All nine formulations of in-situ ocular gel were subjected to evaluation. Out of 9 formulations, F3 had a good gelling capacity with the minimum amount of polymer. The appearance of the optimized formulation was translucent and homogenous. The pH of the F3 formulation is 5.55±0.07, which is good for maintaining formulation in the solution stage. Viscosity at 20 RPM of F3 formulation at pH 5.5 is 837.30±1.00 cps; this range of viscosity has good flow properties. Viscosity at 20 RPM of F3 formulation at pH 7.4 is 6800.74±1.58cps; this range of viscosity has a good gelling capacity which helps to drug retain at the eye surface. Drug content is 100.16±0.53%. Drug release at 300 min is 69.22±2.12, it can say that the drug may be retained for more than 300 min at the eye surface, which is good for reducing dosing frequency. Conclusion: CTZ was successfully formulated in pH triggered in-situ gelling system using Carbomer 974P in combination with HPMC E4M. The prepared in-situ gel is easily converted from solution stage to gel stage at the pH of the eye so we can say that the drug in the in-situ ocular gel is more bioavailable than conventional ophthalmic solution In vitro results indicated that the in-situ gel system is a viable alternative to conventional ocular drops by virtue of its ability to sustain drug release.